Prospective evaluation of anesthetic protocols during pediatric ophthalmic surgery. Issue 6 (November 2019) - Ducloyer, Jean-Baptiste; Couret, Chloé; Magne, Cécile; Lejus-Bourdeau, Corinne; Weber, Michel; Le Meur, Guylène; Lebranchu, Pierre
Purpose: To date, no protocol of anesthesia for pediatric ophthalmic surgery is unanimously recognized. The primary anesthetic risks are associated with strabismus surgery, including oculocardiac reflex, postoperative nausea and vomiting, and postoperative pain. Methods: This was a prospective, monocentric, observational study conducted in a tertiary pediatric ophthalmic unit. Our anesthetic protocol for strabismus surgery included postoperative nausea and vomiting prevention using dexamethasone and ondansetron. No drug-based prevention of oculocardiac reflex or local/locoregional anesthesia was employed. Results: A total of 106 pediatric ophthalmic surgeries completed between November 2015 and May 2016 were analyzed. The mean patient age was 4.4 (range: 0.2–7.3, standard deviation: 2.4) years. Ambulatory rate was 90%. Oculocardiac reflex incidence was 65% during strabismus surgery (34/52), 50% during congenital cataract surgery (4/8), 33% during intramuscular injection of botulinum toxin (1/3), and 0% during other procedures. No asystole occurred. Postoperative nausea and vomiting incidence was 9.6% after strabismus surgery (5/52) and 0% following the other procedures. One child was hospitalized for one night because of persistent postoperative nausea and vomiting. Postoperative pain generally occurred early on in the recovery room and was quickly controlled. Its incidence was higher in patients who underwent strabismus surgery (27%) than in those who underwent other procedures (9%). Conclusion: Morbidity associated with ophthalmic pediatric surgery is low and predominantly associated with strabismus surgery. The benefit–risk ratio and cost-effectiveness of oculocardiac reflex prevention should be questioned. Our postoperative nausea and vomiting rate is low, thanks to the use of a well-managed multimodal strategy. Early postoperative pain is usually well-treated but could probably be more effectively prevented.